Impact of edapho-climatic factors on the dynamics of VAM root colonization and spore density in three forest tree species of Western Ghats, India - K., Udaiyan (Universiti Putra Malaysia Press, 1996)
A survey was carried out to evaluate the diversity of VAMfungi associated with three exotic forest tree species, Eucalyptus grandis Hill ex. Maid, Grevillea robusta A. Cunn. and Tectona grandis Lf in the Western Ghats ecosystem, South India. The samples were collected from two locations, Kodaikanal (1500 m A.S.L.) and Siruvani (700 m A.S.L.) from January 1992 to June 1993. Climatic factors, physico-chemical properties of rhizosphere soils and VAMF spore counts and root colonization were recorded. Species isolated were Acaulospora, Gigaspora, Glomus, Sc1erocystis and Scutellospora with Glomus constituting 73% of the total species recorded. The mycorrhiza spore density was maximum from January to June in all samples collectedfrom all three tree species at both sites. High root colonization was recorded between the months of September and November. In both sites, the spore density was positively correlated with temperature and negatively with rainfall and soil moisture. The reverse was recorded for root colonization. There was positive correlation between vesicle number and spore number.